Study of Budget Efficiency Related to Covid-19 Hospitalization Claim Policy in X Hospital Malang: A Case Study - Fitriasari, Nikma; Hariyanto, Engelbert; Kodriyah, Lailatul; Retno Suryaningati, Engelbertha; Silvaira, Natasya (Jurnal Kedokteran Brawijaya, 2024)
Coronavirus Disease 2019 (Covid-19) infection spread rapidly to more than 114 countries. Covid-19 spreading has a tremendous effect socially and economically, Indonesia included. Indonesian Government was issuing regulations about Technical Claim Instructions for anticipation. This Technical Claim Instruction was regulated on Keputusan Menteri Kesehatan (KMK) No HK 01.07/Menkes/238/2020, then renewed on KMK No HK.01.07/Menkes/446/2020. The purpose of this research is to analyze budget efficiency related to the change of Covid-19 hospitalization claim regulation. The research was done retrospectively, using secondary data such as claims and patient's medical records. Research conducted in October 2020 on X Hospital. The research sample used was every Covid-19 patient from March to September 2020 totaling 146. The data were analyzed using chi-square with the result showing that there is no correlation between changes of technical claim regulation with budget efficiency.